Meta-Analysis of the Effect of the Reciprocal Teaching Learning Model on the Mathematical Communication Ability of Junior High School Students - Rizka Rahmadanty Marpaung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the influence of the Reciprocal Teaching learning model on the mathematical communication skills of junior high school students. The method used is meta-analysis, namely systematic research by analyzing research results that have been published nationally related to the effect of the reciprocal teaching learning model on junior high school students' mathematical communication abilities. The sample for this study were six national journal articles published in the 2013-2022 range at the junior high school level, which discussed writing experiments on the effect of the reciprocal teaching learning model on junior high school students' mathematical communication abilities. The instrument in this study was a coding sheet that summarized the data and information of the journal articles studied. The results showed that overall the ten journal articles had an average effect size value of 1.14, which means that they belong to the large effect category. The results of the study also show that the reciprocal teaching learning model has a great influence on mathematical communication skills in terms of class levels, subject matter, and regions in Indonesia. This shows the conclusion that the reciprocal teaching learning model has a major influence on students' mathematical communication skills compared to conventional learning.